Addition of anti-estrogen therapy to anti-HER2 dendritic cell vaccination improves regional nodal immune response and pathologic complete response rate in patients with ERpos/HER2pos early breast cancer. (2nd September 2017) - Lowenfeld, Lea; Zaheer, Salman; Oechsle, Crystal; Fracol, Megan; Datta, Jashodeep; Xu, Shuwen; Fitzpatrick, Elizabeth; Roses, Robert E.; Fisher, Carla S.; McDonald, Elizabeth S.; Zhang, Paul J.; DeMichele, Angela; et al.
ABSTRACT: HER2-directed therapies are less effective in patients with ER pos compared to ER neg breast cancer, possibly reflecting bidirectional activation between HER2 and estrogen signaling pathways. We investigated dual blockade using anti-HER2 vaccination and anti-estrogen therapy in HER2 pos /ER pos early breast cancer patients. In pre-clinical studies of HER2 pos breast cancer cell lines, ER pos cells were partially resistant to CD4 + Th1 cytokine-induced metabolic suppression compared with ER neg cells. The addition of anti-estrogen treatment significantly enhanced cytokine sensitivity in ER pos, but not ER neg, cell lines. In two pooled phase-I clinical trials, patients with HER2 pos early breast cancer were treated with neoadjuvant anti-HER2 dendritic cell vaccination; HER2 pos /ER pos patients were treated with or without concurrent anti-estrogen therapy. The anti-HER2 Th1 immune response measured in the peripheral blood significantly increased following vaccination, but was similar across the three treatment groups (ER neg vaccination alone, ER pos vaccination alone, ER pos vaccination + anti-estrogen therapy). In the sentinel lymph nodes, however, the anti-HER2 Th1 immune response was significantly higher in ER pos patients treated with combination anti-HER2 vaccination plus anti-estrogen therapy compared to those treated with anti-HER2 vaccination alone. Similar rates of pathologic complete response (pCR) were observed in vaccinated ER neg patients and vaccinated ER pos patients treated with concurrent anti-estrogen therapy (31.4% vs. 28.6%); both were significantly higher than the pCR rate in vaccinated ER pos patients who did not receive anti-estrogen therapy (4.0%, p = 0.03). Since pCR portends long-term favorable outcomes, these results support additional clinical investigations using HER2-directed vaccines in combination with anti-estrogen treatments for ER pos /HER2 pos DCIS and invasive breast cancer.